Measurement of the charged-particle multiplicity inside jets from [Formula: see text][Formula: see text] pp collisions with the ATLAS detector - Atlas Collaboration; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; Abolins, M; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; et al. (The European physical journal. C, Particles and fields, 2016)
The number of charged particles inside jets is a widely used discriminant for identifying the quark or gluon nature of the initiating parton and is sensitive to both the perturbative and non-perturbative components of fragmentation. This paper presents a measurement of the average number of charged particles with [Formula: see text] [Formula: see text] inside high-momentum jets in dijet events using 20.3 fb[Formula: see text] of data recorded with the ATLAS detector in pp collisions at [Formula: see text] [Formula: see text] collisions at the LHC. The jets considered have transverse momenta from 50 [Formula: see text] up to and beyond 1.5 [Formula: see text]. The reconstructed charged-particle track multiplicity distribution is unfolded to remove distortions from detector effects and the resulting charged-particle multiplicity is compared to several models. Furthermore, quark and gluon jet fractions are used to extract the average charged-particle multiplicity for quark and gluon jets separately.